South-North convergence from a new perspective - Michael Hübler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
This North-South model of Schumpeterian endogenous growth combines a market, productivity and knowledge effect. A set of various convergent and divergent growth paths is derived that is much richer than in the literature so far. South-North convergence based on North-South technology diffusion through intermediate goods trade is guaranteed if the knowledge effect dominates the productivity effect. Moreover, a larger Southern market expands the area of convergence and can prevent divergence. Not only a larger Southern market size, but also a higher Southern steady state growth rate benefit the North so that convergence is desirable for both, the South and the North.
urn:nbn:de:bsz:180-madoc-352786
Keywords: F18; O11; O33; O41; 330; Schumpeter; endogenous growth; technology diffusion; convergence; poverty trap